Google Spreadsheet Training for Teacher at SMK N 1 Padang Cermin - Heni Sulistiani; Fikri Hamidy; Auliya Rahman Isnain; Ikbal Yasin; Rika Mersita; Yunita Yunita; Yasinta Ismi (Journal of Engineering and Information Technology for Community Service, 2022)
A teacher is a professional educator who educates, teaches a knowledge, guides, trains, provides assessments, and evaluates students. Teachers not only teach formal education, but also other education and can be an exemplary figure by their students. Teacher competencies as referred to in the law include pedagogical competence, personality competence, social competence, and professional competence obtained through professional education. Google Sheets is a web-based software developed by Google, for creating tables, simple calculations, or data processing. Google spreadsheets have a shape and appearance that is not much different from Microsoft Excel. The conclusion that can be drawn from the implementation of the PKM of the Assisted Schools is that training activities in the form of using Google Sheets for financial statement management for teachers majoring in Accounting on April 14, 2022 were carried out well and the result was that teachers became more understanding of making financial reports using Google spreadsheets, so as to be able to provide knowledge and improve their ability to make financial reports.